2015
DOI: 10.1002/macp.201400541
|View full text |Cite
|
Sign up to set email alerts
|

Fiber‐Like Micelles from the Crystallization‐Driven Self‐Assembly of Poly(3‐heptylselenophene)‐block‐Polystyrene

Abstract: The crystallization-driven self-assembly (CDSA) of crystalline-coil polyselenophene diblock copolymers represents a facile approach to nanofi bers with distinct optoelectronic properties relative to those of their polythiophene analogs. The synthesis of an asymmetric diblock copolymer with a crystallizable, π-conjugated poly(3-heptylselenophene) (P3C7Se) block and an amorphous polystyrene (PS) coblock is described. CDSA was performed in solvents selective for the PS block. Based on transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 86 publications
0
50
0
Order By: Relevance
“…28 In the current state-of-the-art, we have the greatest understanding and the greatest degree of control over rodlike micelle formation of PFS diblock copolymers. Using the seeded growth protocol, 29 one adds a concentrated solution of unimer in a good solvent to a suspension of micelle seed fragments in a selective solvent.…”
Section: Cmentioning
confidence: 99%
“…28 In the current state-of-the-art, we have the greatest understanding and the greatest degree of control over rodlike micelle formation of PFS diblock copolymers. Using the seeded growth protocol, 29 one adds a concentrated solution of unimer in a good solvent to a suspension of micelle seed fragments in a selective solvent.…”
Section: Cmentioning
confidence: 99%
“…1 : 5 -1 : 20, cylindrical micelles are formed, whilst platelets form at block ratios closer to 1 : 1. 28 CDSA been reported for a variety of crystallizable polymers, 29,[31][32][33][34][35] including conjugated materials, [36][37][38] and molecular species that self-assemble by non-covalent πstacking interactions. 39,40 In collaboration with Winnik and coworkers we have shown that a key advantage of CDSA over the self-assembly of BCPs with an amorphous core-forming block is that the termini of many micelles with crystalline cores remain active towards the addition of further incoming BCP unimer via an epitaxial growth mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The first examples of rodlike core-crystalline micelles were reported almost 20 years ago for poly(ferrocenyldimethylsilane) (PFS) diblock copolymers. [5][6][7] Since that time, particularly after poly(3-heptylselenophene), 32 poly(L-lactide) [33][34][35] and poly(ferrocenyldimethylgermane)9 as the core-forming block. Compared to block copolymers that form 2D platelet crystals, we have a much poorer understanding of how the semicrystalline polymer chains pack in the core of 1D…”
Section: Introductionmentioning
confidence: 99%